PERAN GURU DALAM PENGENALAN SAINS PADA ANAK KELOMPOK B2 DI TK BINA SARI - Octaviani, Dhitia; Usman, Usman; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe introduction of science taught in early childhood is to classify by function, to demonstrate explorative activity and to investigate, to plan the activities to be performed, to recognize environmental causes, to show initiative in choosing themes, and to solve simple problems. The role of teachers in learning science introduction gives a great influence on the ability of children in achieving the goals and benefits of learning science. This is why researchers want to examine how the role of teachers in the application of science recognition in children aged 5-6 Year Group B2 in TK Bina Sari Pontianak City and how the results of the introduction of science in children aged 5-6 Year Group B2 in TKBina Sari Pontianak City. The method used in this research is descriptive with qualitative approach. The location of the research was conducted in TK Bina Sari Pontianak Kota.Sumber of data derived from interviews of two teachers in Class B2, observation and documentation in the field. The results of this study indicate that the role of teachers in the introduction of science in children aged 5-6 years in kindergarten Bina Sari Pontianak City, teachers make a plan of daily learning (RPPH). In making a learning implementation plan, teachers determine the activities to be implemented and prepare the media / learning resources needed. Teachers also do the arrangement of the environment by arranging the classroom and putting the learning media to be used, the introduction of science to children aged 5-6 years in the Pontianak City Bina Sari kindergarten, the teacher gives a foothold before doing science experiments and stepping during science experiment activities take place, teachers provide a foothold after doing science experiments on children and make notes and assessments of the progress of child development.Â Keywords: introduction of science, early childhood, the role of teachers